Wax, sex and the origin of species: Dual roles of insect cuticular hydrocarbons in adaptation and mating. (19th May 2015) - Chung, Henry; Carroll, Sean B.
<x xml:space="preserve">Abstract</x> Evolutionary changes in traits that affect both ecological divergence and mating signals could lead to reproductive isolation and the formation of new species. Insect cuticular hydrocarbons (CHCs) are potential examples of such dual traits. They form a waxy layer on the cuticle of the insect to maintain water balance and prevent desiccation, while also acting as signaling molecules in mate recognition and chemical communication. Because the synthesis of these hydrocarbons in insect oenocytes occurs through a common biochemical pathway, natural or sexual selection on one role may affect the other. In this review, we explore how ecological divergence in insect CHCs can lead to divergence in mating signals and reproductive isolation. We suggest that the evolution of insect CHCs may be ripe models for understanding ecological speciation.